Research trends of protein palmitoylation in cancer from 2004 to 2024: a bibliometric and visualization analysis - Peng, Yufeng; Peng, Kewei; Wang, Yi; Li, Luyao; Lu, Yuefei (Frontiers in Oncology, 2025)
BackgroundProtein palmitoylation is a dynamic and reversible lipid modification that has attracted increasing attention in cancer research in recent years. Palmitoylation involves the covalent attachment of palmitic acid (C16) to cysteine residues, altering the protein’s hydrophobicity and thereby affecting its membrane localization, stability, and functional activity. Recently, palmitoylation has been closely associated with the development and progression of various cancers, making it a key factor in cancer biology research.MethodsThis study conducted a systematic bibliometric analysis using the Web of Science Core Collection (WoSCC) as the data source. A total of 685 papers published between January 1, 2004, and December 31, 2024, on the relationship between protein palmitoylation and cancer were selected. Information such as article titles, abstracts, and keywords was extracted to analyze publication trends, research hotspots, and collaboration networks among authors and institutions, thus assessing the dynamics of research in this field.ResultsThe analysis revealed that from 2004 to 2024, a total of 685 papers were published on the relationship between protein palmitoylation and cancer, with a significant increase in publications after 2020. The United States and China are the leading countries in this field, with institutions like Harvard University and the Chinese Academy of Sciences making substantial contributions. Research hotspots have shifted from early mechanistic studies to cancer-specific applications, particularly in areas such as tumor immune evasion, metabolic reprogramming, and therapeutic strategies, where significant progress has been made.ConclusionFuture efforts should concentrate on three primary directions: constructing high-resolution pan-cancer palmitoylation site maps to unveil subtype-specific modification patterns; developing subtype-selective inhibitors targeting the ZDHHC enzyme family to overcome the toxicity limitations of current broad-spectrum inhibitors; and establishing international research alliances to integrate China’s high productivity with the United States’ translational expertise, thereby bridging regional disparities between basic research and clinical innovation, ultimately advancing palmitoylation regulatory networks toward precision therapeutic strategies.